Coughing in Small Animal Patients - Hsieh, Brisa M.; Beets, Alicia K. (Frontiers in Veterinary Science, 2020)
Coughing is one of the most common complaints in human medicine. In veterinary medicine, coughing is an equally large problem and one that plays a significant role in the owner’s perception of their pet’s quality of life. In human and veterinary medicine, therapy for chronic cough is often ineffective. The complexity of the cough pathway and variances between species have made it difficult to develop an effective antitussive agent. Of the few effective antitussive agents currently available, there are significant adverse effects. However, there are several promising drugs currently in clinical trials. This article concentrates on the pathophysiology of cough, diagnostics to discover the etiology of the cough, and reviews current treatments, as well as novel therapies currently undergoing research for coughing.